Elucidation of the vasorelaxation mechanisms induced by syzygium polyanthum leaves aqueous extract - Hairul, Nuriana Munirah (2021)
Previous studies have demonstrated that aqueous extract of Syzygium polyanthum leaves (AESP) has vasorelaxation activity. However, there is still very little information on its mechanism of action on direct vasorelaxation activity. Therefore, the present study was designed to determine endothelium-dependant relaxation of the AESP and investigated the mechanism of vasorelaxation. The in vitro method was utilised, mounting the aortic ring into myograph, precontracted with phenylephrine (1 μM) and studied based on the agonist-antagonist inhibition protocols. The endothelium-dependant was studied on endothelium intact and denuded thoracic arterial ring isolated from Wistar-Kyoto (WKY) rats. The vasorelaxation mechanisms of AESP were evaluated on the endothelial-intact aortic rings. This study shown that the AESP relaxation was endothelium-dependant. The vasorelaxant effect of AESP was attenuated by L-NAME (endothelial nitric oxide synthase/eNOS inhibitor, 100 μM) and ODQ (soluble guanylate cyclase/sGC inhibitor, 10 μM). However, methylene blue (cyclic guanosine monophosphate/cGMP lowering agent, 10 μM) and indomethacin (non-selective COX inhibitor, 10 μM) did not produce significant inhibition on the AESP relaxation. Taken together, the findings indicated that vasorelaxation of AESP was endothelium-dependent, through NO/eNOS and sGC pathways.